The Influence of Learning Strategies and Motivation Learning on the Results of Learning Ability Min Sei Mati Medan - Rusydi Ananda (Britain International for Academic Research (BIAR) Publisher, 2019)
This study aims to find out and to stress: (1) the effect of the application of learning strategies on students' Akidah Akhlah learning outcomes, (2) theeffect of learning motivation on student Akidah Akhlah learning outcomes, and (3) the interaction between learning strategies and learning motivation towards Akidah Akhlak learning outcomes. The population of this study was all students in class V MIN Sei Mati Medan consisting of 3 classes. Based on Cluster Random sampling techniques. The research instrument is a test used to obtain learning outcome data and questionnaires to obtain data on student learning motivation. The analysis technique is two-way Anova at significance α = 0.05 followed by the Scheffe test. The results showed: (1) the average learning outcomes of students taught with collaborative learning strategies higher than the average learning outcomes of students taught with competitive learning strategies, (2) the average learning outcomes of students with high learning motivation higher than the learning outcomes of students with low learning motivation, and (3) there is an interaction between learning strategies and learning motivation towards Akidah Akhlak learning outcomes.